Investigating the encapsulation of lead bromide perovskite with poly(3-bromothiophene) for improved aqua stability and enhanced fluorescence memory - Debasis Brahma; Jit Satra; Sayan Basak; Subhadeep Chakraborty; Rahul Chatterjee; Suman Acharya; Debdipta Basu; Abhijit Bandyopadhyay (Royal Society Open Science)
Formamidinium lead bromide (FAPbBr₃) perovskites are promising candidates for optoelectronic applications owing to their exceptional semiconducting and photoluminescent properties. However, their high sensitivity to environmental factors like moisture and polar solvents limits their long-term stability, posing a barrier to commercial applications. This study addresses this stability challenge by encapsulating FAPbBr₃ in poly(3-bromothiophene) (PTBr), a high molecular-weight-conducting polymer, to enhance resistance to aqueous and solvent-based degradation. The PTBr encapsulation was found to significantly improve the thermal and environmental stability of FAPbBr₃, as evidenced by thermogravimetric analysis, which revealed a reduced and delayed mass loss and an increased residual mass (up to 28.17% in composites with 70% PTBr content). Photoluminescence studies demonstrated that the encapsulated composites exhibited a mean fluorescence lifetime of 87.4 ns, compared with 12.56% fluorescence retention in unencapsulated FAPbBr₃ after exposure to moisture for 45 days. Moreover, encapsulated FAPbBr₃ retained over 80% of its green light fluorescence intensity even after 1 year, whereas the unencapsulated sample degraded to less than 5%. Notably, the composites displayed fluorescence recovery upon exposure to polar solvents, further highlighting PTBr’s protective role. These findings provide a practical, non-interacting encapsulation strategy that enhances both the environmental and thermal stability of FAPbBr₃ while preserving its emission characteristics, offering potential to support the further development of perovskite-based optoelectronic devices for practical applications.